2022
DOI: 10.1155/2022/7391258
|View full text |Cite
|
Sign up to set email alerts
|

An English Flipped Classroom Teaching Model Based on Big Data Analysis

Abstract: In order to improve the defect that the quality of English flipped classroom teaching cannot be quantitatively evaluated, an English flipped classroom teaching model based on big data learning analysis is proposed. In the English flipped classroom teaching mode, which applies the flipped classroom teaching mode, the classroom teaching links are changed, the preview feedback, joint answer and question between teachers and students, classroom teaching, and teachers’ questions are taken as the key links of classr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Scholars from the United States, Spain, and China have some strengths in this area and dominate the research component, but collaboration between different groups is relatively sparse, which may be related to the conduct of different disciplines. For example, some researchers have applied flipped classrooms to medical education (Ruzafa-Martínez et al, 2023;Wade et al, 2023), and other educators have introduced the model to language subjects (Guo et al, 2016;Yin, 2017;Sa et al, 2022) and mechanical engineering (Cho et al, 2021). We look forward to furthering cross-collaboration to promote the development of flipped classroom-related research.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars from the United States, Spain, and China have some strengths in this area and dominate the research component, but collaboration between different groups is relatively sparse, which may be related to the conduct of different disciplines. For example, some researchers have applied flipped classrooms to medical education (Ruzafa-Martínez et al, 2023;Wade et al, 2023), and other educators have introduced the model to language subjects (Guo et al, 2016;Yin, 2017;Sa et al, 2022) and mechanical engineering (Cho et al, 2021). We look forward to furthering cross-collaboration to promote the development of flipped classroom-related research.…”
Section: Discussionmentioning
confidence: 99%
“…[2] This student-centered approach to learning has generated substantial interest in higher education and has been applied in fields such as nursing education, mathematics education, English language learning and teaching, mechanical engineering, and others. [3][4][5][6] Studies have indicated mixed results for academic outcomes and student satisfaction in the nursing field, but positive engagement was achieved when instructors rationalized the purpose of the flipped classroom approach to students. [3] Additionally, current research trends in flipped language classrooms focus on integrating e-tools and learning content into language teaching and learning activities.…”
Section: Introductionmentioning
confidence: 99%